Modulation of Dendritic Cell Maturation by Fasciola hepatica: Implications of Glycans and Mucins for Vaccine Development - Noya, Veronica (2014)
Fasciola hepatica is a worldwide distributed helminth pathogen that causes great economic losses in sheep andcattle. This parasite is able to regulate the host immune response, producing high levels of IL-5 and low levels ofIFNγ, as well as modulating the function of dendritic cells (DCs), mast cells or macrophages, among others.Moreover, TLR-mediated maturation of DCs can be suppressed by F. hepatica derived components. Here, weinvestigated the role of glycans in the modulation of LPS-induced maturation of DCs, as well as in the production ofIL-5 and IFNγ by splenocytes from infected mice. We show that F. hepatica induces the recruitment to theperitoneum of semi-matured DCs, as judged by a down-regulation of MHC class II molecule expression and anincrease of CD80 and CD86 expression of DCs in the peritoneum of infected animals. Furthermore, we provideevidence indicating that glycan structures from F. hepatica are responsible, at least in part, for inhibiting LPS-induced DC maturation and production of IFNγ by splenocytes from infected animals. On the other hand, we showthat a mucin-like non-glycosylated peptide highly expressed in NEJ (Fhmuc) is able to synergize with LPS ininducing DC-maturation, and that it induces a T cell response specific for F. hepatica, both alone or in combinationwith DCs. Our data highlight the role of F. hepatica glycans in modulating the host immune response and mightcontribute to the design of vaccines against fasciolosis.